Ethnography of a parasite: A quantitative ethnographic observation of forest malaria in the Amazon basin (2019)
Aims: Malaria in the Amazon basin is persistently more prevalent among low density populations (1–4 people/km2). Describing malaria transmission in small populations, such as ethnic minorities in the Amazon basin, living in reserves in groups that amount to 110–450 individuals, is fundamental for the implementation of adequate interventions. Here, we examine malaria transmission in a context of high prevalence in a small population of Nükak ethnicity (ethnic group n = 400 ? 650 individuals, study group, n=108 individuals) living in the peri-urban area of a city with 35,000 inhabitants in the Amazon basin. Methods: Using methods from behavioral ecology, we conducted a quantitative ethnography and collected data to inform of individual behavioral profiles. Individual malarial infection reports were available from the local public health offices, so each behavioral profile was associated with an epidemic profile for the past 5 years. Results: Our research shows that, in-line with current opinion, malaria among the Nükak is not associated with an occupational hazard risk and follows a holoendemic pattern, where children are most susceptible to the parasite. Parasite loads of malarial infection among the Nükak persist at much higher rates than in any other neighboring ethnicity, which indicates an association between high incidence rates and endemicity. Conclusions: We hypothesize that malarial infection in the forest follows a pattern where the parasite persists in pockets of holoendemicity, and occupational hazard risk for individuals outside those pockets is associated with behaviors that take place in the proximity of the pockets of endemicity. © Author(s) 2018.